2016
DOI: 10.1021/acs.macromol.6b02078
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene (Co)polymerization by Binuclear Nickel Phenoxyiminato Catalysts with Cofacial Orientation

Abstract: A series of neutral binuclear nickel phenoxyiminato catalysts connected by rigid skeletons of different lengths have been efficiently synthesized. The rigid skeleton and bulky tert-butyl groups together force two nickel coordination planes to get close and stack in an anti cofacial fashion. With reduced nickel−nickel distances, these binuclear nickel complexes displayed higher catalytic activity, produced polymers with higher molecular weight, and showed less inhibition by the presence of additional polar mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
(66 reference statements)
1
38
1
1
Order By: Relevance
“…Ligands do have critical influences on the ethylene polymerization process, thus greatly influencing the microstructures of the resulting polymers . Ligands such as α‐diimines,[4f], , [15b], , , phosphine‐sulfonates,, [15a], salicylaldimines,, , [15d], [19a], and iminopyridines, forming five‐ or six‐membered chelate rings with the metal center are still common for catalyst design because of their higher stability, and modification of ligands in substituents and backbone is a common – but not easy – way to design new, high‐performance catalysts. In fact, there are still some examples of failed attempts to design catalysts with special performances, as can be seen from recent reports …”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands do have critical influences on the ethylene polymerization process, thus greatly influencing the microstructures of the resulting polymers . Ligands such as α‐diimines,[4f], , [15b], , , phosphine‐sulfonates,, [15a], salicylaldimines,, , [15d], [19a], and iminopyridines, forming five‐ or six‐membered chelate rings with the metal center are still common for catalyst design because of their higher stability, and modification of ligands in substituents and backbone is a common – but not easy – way to design new, high‐performance catalysts. In fact, there are still some examples of failed attempts to design catalysts with special performances, as can be seen from recent reports …”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
“…Inspired by enzyme catalytic performances, recent progress has revealed several examples of the utilization of secondary coordination sphere interactions and metal–metal cooperativity to affect or to modulate the performance of ethylene polymerization. [27b], , Certainly, metal–metal cooperativity can be called secondary coordination sphere interactions in cases in which one metal is not the main active center in a heterometallic catalyst.…”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
“…The distance between the centres and the steric hindrance around the active sites are two main factors controlling the cooperative effect . Moreover, the presence of aromatic bridges in binuclear catalysts leads to increasing thermal stability, and steric and electronic effects . Marks and co‐workers reported that binuclear complexes bearing rigid structure and proximate centres lead to higher productivities and methyl branch selectivity than their mononuclear analogues .…”
Section: Introductionmentioning
confidence: 99%
“…[23] Discussion on the critical factors that enable controlled polymerizations in CTP has been thoroughly detailed in reviews. [24][25][26] Interestingly, one area that has not been relatively explored at all in CTP, and may be useful, is multimetallic cooperative catalysis.Multimetallic cooperative catalysts have been employed to improve the quality of olefin [27][28][29] and epoxide [30] polymers (Figure 1). In these studies, the geometry of the bimetallic catalysts and the proximity of the metal centers were suggested to have critical influence on catalytic rates, branching, chain transfer, and control over molecular weight and dispersity.…”
mentioning
confidence: 99%
“…Structures of bimetallic catalysts used for olefin and epoxide polymerizations [27][28][29][30]. Synthesis of P3HT via KCTP.…”
mentioning
confidence: 99%